Needs Analysis for Development of E-Modules as Teaching Materials to Improve Archive Digitalization Competence - Afifah Dwi Nur Illahi; Djono Djono; Sri Sumaryati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
The digital era which is developing very rapidly apart from providing convenience also requires village officials to have technological expertise to adjust to environmental changes as a consequence of changes in existing policies. Therefore, this study aims to (a) identify competency problems in digitizing archives and (b) analyze module development needs. This study uses a quantitative design approach, using a survey to collect responses from respondents. Questionnaires were distributed to 10 village apparatus as learning society or training student respondents using random sampling technique. The collected data were analyzed descriptively. The results of the study show that overall the level of problems in the competency of digitizing village archives is high from various aspects. Participants have the desire to develop e-modules with complete content and display that is not monotonous. Therefore, it is proposed that this e- module be developed to meet user needs, so that the goal of implementing archive digitization can be achieved.